Disrupting Migraine Dynamics: A Narrative Review of the Consequences of Modern Anti-CGRP Monoclonal Antibody Therapies - Dawn C. Buse; Jan Versijpt; Hans-Christoph Diener (Neurology and Therapy)
Abstract This article provides an overview of a symposium held as part of the proceedings at the 10th European Academy of Neurology Congress in Helsinki, Finland, on 2 July 2024. Migraine is a common neurological disease and a leading cause of disability worldwide. Anti-calcitonin gene-related peptide (CGRP) therapies are the first to be specifically developed for migraine prevention and are recommended as a first-line option by the American Headache Society and European Headache Federation. Data on the effectiveness of anti-CGRP therapies are now available from clinical trials and real-world studies, and this article briefly reviews these data and discusses what they mean for people with migraine, and how healthcare professionals can take the conversation back to their clinics.